Lactate in skin homeostasis: metabolism, skin barrier, and immunomodulation - Ruan, Dandan; Hu, Tingting; Yang, Xuefan; Mo, Xiaohui; Ju, Qiang (Frontiers in Immunology, 2025)
Lactate, once considered merely a byproduct of glycolysis, is now increasingly recognized as a multifunctional signaling molecule with roles beyond energy metabolism. It functions as an enzyme cofactor and binds to specific receptors to modulate cellular functions. In the skin, lactate is produced by various cell types. It is then transferred between cells or to the extracellular space, helping to balance cellular pH and to provide signals that regulate skin barrier and skin immunity. Additionally, lactate/lactate-related genes hold promising therapeutic potential for the treatment of skin tumors, inflammatory skin diseases, hair loss, and in cosmetic dermatology. This article highlights the latest advances in our understanding of lactate’s biological effects on the skin and explores its therapeutic potential, offering insights into future research directions.